Direito ao planejamento entre o desenvolvimento nacional e a austeridade fiscal : proposição de modelagem de políticas econômicas aplicada ao orçamento das universidades federais brasileiras - Lima Junior, Francisco Gaspar de (2024)
The central object of this thesis is the definition of the right to Planning as a parameter that guarantees Development in the face of fiscal austerity, examined from the perspective of sustainable budget modeling for Brazilian federal universities. The main objective of the research is to investigate the structuring mechanisms for guaranteeing instrumental freedoms in relation to the submission of economic policies. The study proposes to expose the current impasse between fiscal austerity and the guiding normativism of the Constitution of the Federative Republic of Brazil and its status as an Economic Constitution, in order to articulate the normative content of Development with the submission of economic policy to constitutional postulates. To examine them, the inflationary metric of the public spending ceiling is observed within the scope of the budget demand of federal universities given the manifestation of austerity limiting its maintenance as an expression of fiscal policies, with a focus on Planning and its systematic interpretation. The research seeks to answer how the right to Planning can act as a normative instrument capable of limiting the orientation of political-economic arrangements that demonstrably compromise social rights, especially regarding the congruence of the developmental State as a normative agent and regulator of economic activity. The theoretical framework is based on the concept of Economic Constitution, constitutionally adopted ideology and developmental State, associated with intervention in the economic domain, present in the epistemological field of Economic and Constitutional Law. Using a critical-methodological and legal-dogmatic approach, the research adopts an inductive reasoning based on the analysis of data, reports and projections obtained through information collected in the official systems of the federal government via the Integrated Planning and Budget System – SIOP, Institute of Applied Economic Research – IPEA and Treasury Management, in addition to data available from the National Association of Directors of Federal Higher Education Institutions - ANDIFES and the Transparency Portal. This thesis is legal-propositional, conducting a qualitative analysis of the doctrinal and documentary elements for the systematization of the Right to Planning.